Hadith Hermeneutic of Ali Mustafa Yaqub - Rohmansyah, Rohmansyah (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2017)
Hermeneutic hadith is disputed by academics; some refuse, others develop the theory (as long as it does not conflict with the source of Islamic teachings when the theory is used in the text of the hadith). The hermeneutics of hadith are from the West used in the Bible. The research method used is the library research with hermeneutical interpretation approach and produce several things, such as: First, in terminology, hadith according to Ali Mustafa Yaqub is a source of Islamic teachings both derived from the words, deeds and the characteristics of the Prophet Muhammad. The characteristics of the Prophet Muhammad are part of the sunnah. Secondly, in understanding the text of the traditions of the Prophet Muhammad is not only taken from the literary meaning, but must look for other meanings so that the text of hadith can be fully understood. Comprehensive understanding of hadith can be done by looking at the background of the emergence of Hadith (asbâb al-Wurûd), local and temporal (zamāni wa makâni), sentence causality ('illat al-kalam) and socio-cultural (taqâlid). Hermeneutic Gadamer states that the application of the hadith understanding can be understood as part of the hermeneutical process of hadith, although Ali Mustafa Yaqub does not explicitly explain the hermeneutic theory used in the understanding of a hadith text.